Synthesis and Physical Characterization of Nano-Hydroxyapatite-Collagen-Epigallocatechin-3-Gallate Hydrogel Composite - Amanda, Hiroko Gabriela; Elline, Elline; Fibryanto, Eko (Journal of Indonesian Dental Association, 2022)
Introduction: Most commonly used vital pulp therapy material is calcium hydroxide (Ca(OH)2) but it has several disadvantages. Previous studies found that nano-hydroxyapatite might induce reparative dentin with no tunnel defect and adding collagen can improve hydroxyapatite mechanical properties. The collagen can also increase pulp cell proliferation and differentiation. The addition of Epigallocatechin-3-Gallate (EGCG) to collagen gel can be beneficial in reducing pulp inflammation. Objective: The purpose of this study is to synthesize and analyze the physical characteristics of the nano-Hydroxyapatite-collagen-Epigallocatechin-3-Gallate hydrogel composite. Methods: Nano-hydroxyapatite from chicken egg shells, 0,2 g/mL collagen type I, and 10 mmol/L EGCG each dissolved in 2 mL deionized water with various ratio of nano-hydroxyapatite:collagen, 40:60 (group 1), 50:50 (group 2), and 60:40 (group 3). Each solution was mixed together then 2% HPMC was added into the mixture. In present study, we observed hydrogel composite pH value, gelation time, and injectability analysis. Results: The pH value in 1 hour stirring for each group was 8,05 ± 0,05, 8,43 ± 0,02, and 8,71 ± 0,04. All samples had 1 hour gelation time. Injectability for each group was 90,67%, 91,93%, and 95,03%. Conclusions: The nanohydroxyapatite, collagen and EGCG hydrogel composite has a potential physical characterization to be used as a vital pulp therapy material based on its pH value and injectable ability but further study should be considered in determining ideal gelation time. ABSTRAK Pendahuluan: Bahan perawatan pulpa vital yang paling umum digunakan adalah kalsium hidroksida (Ca(OH)2), tetapi bahan tersebut memiliki beberapa kekurangan. Penelitian sebelumnya menunjukkan nano-hidroksiapatit mampu merangsang pembentukan dentin reparatif tanpa tunnel defect dan penambahan kolagen mampu meningkatkan sifat mekanik hidroksiapatit. Penambahan Epigallocatechin-3-Gallate (ECGC) pada gel kolagen bermanfaat dalam mengurangi respon inflamasi pulpa. Tujuan: Penelitian ini dilakukan untuk mensintesis dan melakukan uji karakteristik fisik komposit hidrogel nano-hidroksiapatit-kolagen-Epigallocatechin-3-Gallate. Metode: Nano-hidroksiapatit dari cangkang telur ayam dilarutkan dengan 0,2 g/mL kolagen tipe I, dan 10 mmol/L EGCG masing-masing ke dalam air deionisasi dengan perbandingan rasio nano-hidroksiapatit dan kolagen, 40:60 (kelompok 1), 50:50 (kelompok 2), dan 60:40 (kelompok 3). Seluruh larutan dicampurkan dan ditambahkan HPMC 2%, lalu dilakukan uji karakteristik gel berupa uji pH, waktu gelasi, dan uji injektabilitas. Hasil: Nilai pH 1 jam setelah pengadukan secara berurutan adalah 8,05 ± 0,05, 8,43 ± 0,02, dan 8,71 ± 0,04 dengan waktu gelasi selama 1 jam. Injektabilitas secara berurutan adalah 90,67%, 91,93%, dan 95,03%. Kesimpulan: Bahan komposit hidrogel nano-hidroksiapatit, kolagen, dan EGCG memiliki karakteristik fisik yang berpotensi untuk digunakan sebagai bahan terapi pulpa vital jika dilihat dari nilai pH dan kemampuan injektabilitas yang diperoleh.